Interstitial Lung Disease as Initial Manifestation of Systemic Lupus Erythematosus - Kumar, A; Khan, U; Shrestha, B; Thapa, S; Rizvi, N (Journal of Nepal Health Research Council, 2013)
Interstitial lung disease (ILD) is a group of disease characterized by fibrosis and scarring of the lung while Systemic Lupus Erythematosus is a multisystem disorder and both of these diseases are of unknown etiologies. Interstitial lung disease, as a presenting feature of SLE without any significant systemic involvement is a unique presentation and this case reports such example. Keywords: interstitial lung disease; systemic lupus erythematosus.